Superhydrophocity via gas-phase monomers grafting onto carbon nanotubes. Issue 2 (May 2016) - Zha, Jinlong; Batisse, Nicolas; Claves, Daniel; Dubois, Marc; Frezet, Lawrence; Kharitonov, Alexander P.; Alekseiko, Leonid N.
Abstract: Superhydrophobic films were prepared using dispersions of fluorinated multi-walled carbon nanotubes (MWCNTs) or nanofibers (CNFs) in toluene. The grafting of polystyrene allowed stable dispersions to be obtained. The grafting of polystyrene (PS), polyacrylic acid (PAA) and polyaniline (PANI) onto nanofibers and MWCNTs was first evidenced by solid state NMR and Infrared Spectroscopy. The graft polymerization of styrene, acrylic acid and aniline monomers was initiated by radicals (dangling bonds) formed due to the initial fluorination. The process appeared as highly versatile and efficient for different polymers. The consumption of those radicals in the course of grafting was evidenced by EPR, through decrease of the spin density. The hydrophobic/hydrophilic character was tuned according to the grafted polymer nature, i.e. hydrophobic with PS or hydrophilic with PAA. Finally, in order to reach superhydrophobicity, films were prepared from CNFs or MWCNTs, irrespective of their average diameter, that allowed adequate structuring of the surface. The presence of fluorine atoms on their surface also favors superhydrophobicity. Water contact angles of 155 ± 2° and 159 ± 2° were measured for the films casted from fluorinated CNFs or MWCNTs with grafted polystyrene, respectively.